Differences in Academic Performance by Grade Span Configuration for Students in Poverty (Global Journal of Human-Social Science, 2016)
In this investigation, the degree to which passing rates on the STAAR Reading and Mathematics assessments of Grade 5 and 6 students in poverty in the state of Texas differed as a function of grade span configuration was examined. Data were obtained from the Texas Education Agency for all Grade 5 and 6 students in poverty who were enrolled in single/double grade level (i.e., Grades 4-5, 5 only, or Grades 5-6) or in multi-grade level (i.e., PreK-6) grade span configurations for the 2012-2013 through the 2014-2015 school years. Inferential analyses revealed the presence of statistically significant differences in reading and mathematics passing rates between the two grade span configurations. Grade 5 and Grade 6 students in poverty had statistically significantly higher reading and mathematics passing rates in multi-grade level schools than in single/double grade level schools. Implications for policy and practice are provided.
Keywords: grade span configuration; academic achievement; poverty; grade 5; grade 6